Предмет: Алгебра,
автор: Аноним
Примеры 5,6,7 сделаете
Приложения:
Ответы
Автор ответа:
1
Ответ:
Объяснение:
5) 3 - 8x + 5 = 3 - 3x - 5x + 5 = 3x ( x - 1 ) - 5 ( x - 1 ) = ( x - 1 ) ( 3x - 5 )
6) 36 - 12x + 1 = - 2 * 6x * 1 + = ( 6x - 2 * 6x * 1 + = ( 6x - 1
7) 2 - 7x + 6 = 2 - 3x - 4x + 6 = x ( 2x - 3 ) - 2 ( 2x - 3 ) = ( 2x - 3 ) ( x - 2 )
Похожие вопросы
Предмет: Обществознание,
автор: Аноним
Предмет: Биология,
автор: angelinakris899
Предмет: Алгебра,
автор: adelinagolu
Предмет: Английский язык,
автор: vikakuprik68
Предмет: Русский язык,
автор: Fotjdk44